Ecuador : Request for an Extended Arrangement Under the Extended Fund Facility-Press Release; Staff Report; Staff Supplement; and Statement by the Executive Director for Ecuador. (IMF Staff Country Reports; Country Report ;, 2020)
On May 1, 2020, the Executive Board approved an RFI (USD 643 million, 67.3 percent of quota), to support the urgent needs of the Ecuadorean economy in the wake of COVID-19 crisis, and the authorities cancelled the three-year Extended Fund Facility arrangement (USD 4.2 billion, 435 percent of quota). The macroeconomic situation has since deteriorated, prompting the authorities to request a 27-month EFF of SDR 4.615 billion (about USD 6.5 billion, 661 percent of quota), to help restore macroeconomic stability, support the most vulnerable groups, and advance the structural reform agenda initiated under the previous EFF.